2010
DOI: 10.1177/0731684410388442
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dielectric behavior of bio-waste reinforced polymer composite

Abstract: Coir dust reinforced polymer composites are prepared with epoxy resin as the matrix. The dielectric parameters (relative permittivity ε′, dielectric loss ε′′), AC conductivity σ, and resistivity ρ of pure epoxy resin and composites with different weight percent of coir dust were obtained in a frequency range of 100 Hz to 1 MHz, and temperature range of 30—150°C. The experimental results show that ε′, ε′′, and σ are increased and ρ is decreased with the addition of coir dust in epoxy resin. It is also observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…e dielectric constant of any material depends upon the polarizability of its molecules and is determined by different contributions: interfacial, dipole, atomic, and electronic polarizations. Interfacial polarization in the composite in�uences the dielectric properties at very low frequencies and usually decreases with increasing frequency [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…e dielectric constant of any material depends upon the polarizability of its molecules and is determined by different contributions: interfacial, dipole, atomic, and electronic polarizations. Interfacial polarization in the composite in�uences the dielectric properties at very low frequencies and usually decreases with increasing frequency [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…From the figures, the dielectric loss has high value for (PVA-NiO-SiC) nanocomposites at low frequency, and it is decreasing when increasing the frequency, this is due to the electric dipoles have sufficient time to align with the applied electric field before the electric field changes its direction; consequently the dielectric constant of nanocomposites is high. At high frequencies, the dielectric constant value decreases due to the shorter time available for the dipoles to align [23]. Fig.…”
Section: Results Anddiscussionmentioning
confidence: 99%
“…Natural fiber (wood waste)-reinforced thermoplastics also offers many advantages including biodegradability, renewable character, low cost, absence of associated health hazards, and low wear of processing equipment, [10][11][12][13] when compared with synthetic fibers. 14,15 Natural fibers have successfully improved the mechanical properties of plastic composites, as the following examples demonstrate. Homkhiew et al 9 investigated the effects of rubberwood content on the mechanical properties of recycled PP composites and found that the modulus and hardness of composites increased linearly with an increase of wood flour loadings in the range of 25-45 wt% wood flour.…”
Section: Introductionmentioning
confidence: 99%